2018
DOI: 10.1159/000485978
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Sparing Treatment for Diffuse Invasive Conjunctival Melanoma

Abstract: The management of patients with diffuse invasive conjunctival melanoma focuses on local tumor control and screening for metastasis. Despite the lack of consensus on the benefit of sentinel lymph node biopsy for these neoplasms, the information obtained by histopathology is useful for tumor staging and treatment planning. Due to the lack of evidence of survival improvement, orbital exenteration is being performed with diminishing frequency. We describe a patient with diffuse invasive conjunctival melanoma and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The SNLB results were negative for tumor (0 of 1 [0%]). 25 4 0 Vuthaluru et al 29 4 0 Lokdarshi et al 17 3 0 Wainstein et al 30 3 0 Baroody et al 6 2 2 Maalouf et al 18 2 0 Aziz et al 5 1 0 Chaves et al 8 1 1 Medina et al 19 1 0 Motomura et al 20 1 0 Rubinstein et al 24 1 0 Schwarz et al 26 1 0 Wilson et al 31 1 0 Eyelid Pfeiffer et al 21 20 6 Ho et al 15 8 1 Harish et al 13 5 0 Hayashi et al 14 2 2 Maalouf et al 18 2 0 Iwata et al 16 1 0 Rubinstein et al 23 1 0 Rubinstein et al 25 1 0 Turell and Char 28 1 0 Wilson et al 31 1…”
Section: Pigmented Epithelioid Melanocytoid Tumormentioning
confidence: 99%
“…The SNLB results were negative for tumor (0 of 1 [0%]). 25 4 0 Vuthaluru et al 29 4 0 Lokdarshi et al 17 3 0 Wainstein et al 30 3 0 Baroody et al 6 2 2 Maalouf et al 18 2 0 Aziz et al 5 1 0 Chaves et al 8 1 1 Medina et al 19 1 0 Motomura et al 20 1 0 Rubinstein et al 24 1 0 Schwarz et al 26 1 0 Wilson et al 31 1 0 Eyelid Pfeiffer et al 21 20 6 Ho et al 15 8 1 Harish et al 13 5 0 Hayashi et al 14 2 2 Maalouf et al 18 2 0 Iwata et al 16 1 0 Rubinstein et al 23 1 0 Rubinstein et al 25 1 0 Turell and Char 28 1 0 Wilson et al 31 1…”
Section: Pigmented Epithelioid Melanocytoid Tumormentioning
confidence: 99%
“…Systemic immunotherapies widely used in cutaneous melanoma for several years could also be beneficial to patients with metastatic CM [ 44 , 112 , 113 , 116 , 117 , 118 ];…”
Section: Future Perspectivesmentioning
confidence: 99%
“…11,21,23,25,32,48,51,53 Few reports regarding the immunological features of this disease are available. [83][84][85][86][87][88] Cao conducted a study to evaluate the PD-1/PD-L1 pathway in conjunctival melanoma. In sections of 27 human conjunctival melanomas, it has been found that 19% of the melanoma cells and 59% of the stromal cells expressed PD-L1 (≥5%) on their membrane.…”
Section: Immune Checkpoint Inhibitors For Conjunctival Melanomamentioning
confidence: 99%
“…87 In the adjuvant setting, ipilimumab was administered to a patient with conjunctival melanoma who did not experience a recurrence for 16 months. 88 Although the limited data, ICIs can be considered for the treatment of advanced conjunctival melanoma.…”
Section: Immune Checkpoint Inhibitors For Conjunctival Melanomamentioning
confidence: 99%